2010
DOI: 10.1002/cpp.719
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between resilience and levels of anxiety, depression, and obsessive–compulsive symptoms in adolescents

Abstract: This study provides further evidence that it may be fruitful for clinicians and researchers to attend to resilience factors in relation to psychological symptoms among older adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
202
2
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(263 citation statements)
references
References 40 publications
36
202
2
11
Order By: Relevance
“…In studies of nearly 400 younger adolescents (aged 13 to 15; Hjemdal et al, 2007), and 300 older adolescents (aged 14 to 18; Hjemdal et al, 2011), higher levels of resilience were associated with lower levels of depressive symptoms. Interestingly, in a sample of 1400 university students, positive cognitions mediated the relationship between resilience and depression such that students with higher levels of resilience had more positive cognitions and lower levels of depressive symptoms (Mak et al, 2011).…”
Section: Cognitive Schemas and Resiliencementioning
confidence: 95%
See 1 more Smart Citation
“…In studies of nearly 400 younger adolescents (aged 13 to 15; Hjemdal et al, 2007), and 300 older adolescents (aged 14 to 18; Hjemdal et al, 2011), higher levels of resilience were associated with lower levels of depressive symptoms. Interestingly, in a sample of 1400 university students, positive cognitions mediated the relationship between resilience and depression such that students with higher levels of resilience had more positive cognitions and lower levels of depressive symptoms (Mak et al, 2011).…”
Section: Cognitive Schemas and Resiliencementioning
confidence: 95%
“…Researchers have begun to integrate resilience constructs into cognitive developmental theories of risk for depression (Hjemdal, Aune, Reinfjell, Stiles, & Friborg, 2007;Hjemdal, Vogel, Solem, Hagen, & Stiles, 2011;Keyfitz et al, 2012;Mak, Ng, & Wong, 2011) to better understand and prevent psychopathology (Masten, 2001;2011). In studies of nearly 400 younger adolescents (aged 13 to 15; Hjemdal et al, 2007), and 300 older adolescents (aged 14 to 18; Hjemdal et al, 2011), higher levels of resilience were associated with lower levels of depressive symptoms.…”
Section: Cognitive Schemas and Resiliencementioning
confidence: 99%
“…Studies have shown that during adolescence people had higher resilience [8]. Hence, resilient people revert and recover their balance sooner after hardship and misfortune.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is a schoolaged child's ability to make friends, engage in academic pursuits, be guided by primary caregivers, and engage in other behaviours acceptable in his or her society, as well as, be resistant to psychological illness, despite experiencing significant adversity (e.g., war, political oppression, poverty, and child abuse). Although initially, resilience theory focused on personal attributes such as self-esteem, self-efficacy, and hardiness [21], resilience is currently recognised as a multidimensional construct including personal characteristics and skills (e.g., active problem solving) as well as external protective factors such as a supportive family and social environment [22]. It is also conceptualised as a dynamic process that fluctuates according to age, gender, individual circumstance and developmental, historical, and cultural context ( [23]; see also [20]).…”
Section: Introductionmentioning
confidence: 99%
“…This may be critical as research has found that poor resilience predicted the development of psychological symptoms such as depression and anxiety [36], moderated the relationship between childhood adversity and psychiatric sequelae [37], or was a strong predictor of positive affect which in turn predicted depression and, to a lesser extent, anxiety [38]. Recent cross-sectional research with Norwegian adolescents has revealed a strong association between diminished resilience and psychological symptoms such as depression and anxiety [22,39]. Thus, the psychological construct of resilience may be a critical element of any interventions to alleviate psychological symptomatology.…”
Section: Introductionmentioning
confidence: 99%